2019
DOI: 10.1093/gbe/evz271
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Plastome Analysis of Root- and Stem-Feeding Parasites of Santalales Untangle the Footprints of Feeding Mode and Lifestyle Transitions

Abstract: In plants, parasitism triggers the reductive evolution of plastid genomes (plastomes). To disentangle the molecular evolutionary associations between feeding on other plants below- or aboveground and general transitions from facultative to obligate parasitism, we analyzed 34 complete plastomes of autotrophic, root- and stem-feeding hemiparasitic, and holoparasitic Santalales. We observed inexplicable losses of housekeeping genes and tRNAs in hemiparasites and dramatic genomic reconfiguration in holoparasitic B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 84 publications
4
44
0
Order By: Relevance
“…It was previously shown that plastid genomes of Balanophoraceae are very AT-rich, with AT contents of currently sequenced genomes being in the range of 86.8%-88.4% (Su et al, 2019; Schelkunov, Nuraliev & Logacheva, 2019; Chen et al, 2020a). This makes them the most AT-rich of any plant genomes, and one of the most AT-rich among all genomes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was previously shown that plastid genomes of Balanophoraceae are very AT-rich, with AT contents of currently sequenced genomes being in the range of 86.8%-88.4% (Su et al, 2019; Schelkunov, Nuraliev & Logacheva, 2019; Chen et al, 2020a). This makes them the most AT-rich of any plant genomes, and one of the most AT-rich among all genomes.…”
Section: Resultsmentioning
confidence: 99%
“…Information about the plastid gene content in Rhopalocnemis phalloides and Balanophora fungosa was obtained from the papers that described their plastid genomes (Schelkunov, Nuraliev & Logacheva, 2019; Chen et al, 2020a). The plastid genome sequences of Daenikera sp.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations